Multifunctional landscapes: Site characterization and field-scale design to incorporate biomass production into an agricultural system. (September 2015) - Ssegane, Herbert; Negri, M. Cristina; Quinn, John; Urgun-Demirtas, Meltem
Abstract: Current and future demand for food, feed, fiber, and energy require novel approaches to land management, which demands that multifunctional landscapes are created to integrate various ecosystem functions into a sustainable land use. We developed an approach to design such landscapes at a field scale to minimize concerns of land use change, water quality, and greenhouse gas emissions associated with production of food and bioenergy. This study leverages concepts of nutrient recovery and phytoremediation to place bioenergy crops on the landscape to recover nutrients released to watersheds by commodity crops. Crop placement is determined by evaluating spatial variability of: 1) soils, 2) surface flow pathways, 3) shallow groundwater flow gradients, 4) subsurface nitrate concentrations, and 5) primary crop yield. A 0.8 ha bioenergy buffer was designed within a 6.5 ha field to intercept concentrated surface flow, capture and use nitrate leachate, and minimize use of productive areas. Denitrification-Decomposition (DNDC) simulations show that on average, a switchgrass ( Panicum Virgatum L .) or willow ( Salix spp.) buffer within this catchment according to this design could reduce annual leached NO3 by 61 or 59% and N2 O emission by 5.5 or 10.8%, respectively, produce 8.7 or 9.7 Mg ha −1 of biomass respectively, and displace 6.7 Mg ha −1 of corn ( Zea mays L.) grain. Therefore, placement of bioenergy crops has the potential to increase environmental sustainability when the pairing of location and crop type result in minimal disruption of current food production systems and provides additional environmental benefits. Graphical abstract: Highlights: Design of a multifunctional landscape by integrating cellulosic biofuel production into an existing agricultural system. The design does not adversely offset current grain production for bioenergy crops. Maps of concentrated flow paths, subsurface flow direction, NO3 –N hotspots, and intra-field corn yield variability. Calibrated DNDC crop parameters for short rotation willows (Salix spp.) are presented for biogeochemical modeling. DNDC model is used to forecast energy crop biomass yield, reductions in leached NO3 –N and N2 O emissions.